Customer Purchasing Decisions: The influence of Price and Brand Image: Study in one Muslim industry in Bandung - Istikomah, Nur; Sidharta, Iwan; Herawati, Octaviane; Najwa, Haritsatun (Informatics Management, Engineering and Information System Journal, 2024)
This research aims to determine the influence of price and brand image on customer purchase decisions. Additionally, this study seeks to analyze the dominant factor between price and brand image affecting customer purchase decisions in the Muslim clothing industry in Bandung. The research focuses on "price and brand image on customer purchase decisions in the Muslim clothing industry in Bandung," involving 89 consumers as the research subjects. Based on the research using path analysis, it is evident that the price variable influences purchase decisions. Furthermore, brand image also affects purchase decisions. The results of the correlation coefficients indicate a strong relationship among all independent variables, namely price and brand image. The conclusion and recommendations based on the research findings suggest paying more attention to price and brand image to enhance customer purchase decisions. The implications of this research highlight the need for businesses to strategically manage their pricing strategies and brand image to attract and retain customers in a competitive market effectively.